A case study on student perception of online lecturing - Wolff-Boenisch, Dom (2021)
This case study looks at implications of transitioning live to recorded lectures, a subject that has acquired an acute importance given COVID19 and the unexpected need to move lectures online. Over a period of six years, from 2015 to 2020, a questionnaire was handed out at the end of a ‘unit’ on environmental geoscience; a ‘unit’ at Australian universities represents a ‘course’ in the European and American tertiary system. This is a 2nd semester, 3rd year core unit of an Applied Geology course meaning that (most of) the polled students were about to acquire a bachelor of science finishing their undergraduate studies. The students were asked multiple questions related to iLectures and their attitude towards this asynchronous content delivery approach as integral part of a flipped classroom. Provided that such a STEM unit with 40-120 students can be deemed representative of the wider student community, the findings indicate that students in general have come to terms with online lectures, way before COVID19 gave them no other choice. Acceptance rates for iLectures were over 50 % across all years, except for 2020, a clear indication that COVID19 marred the online experience, probably due to oversaturation and isolation. The majority of the students saw benefits in this asynchronous lecturing approach, irrespective of whether the rationale behind it had been explained in detail. Despite seeing benefits of the flipped classroom and recorded lectures, one out of three students preferred live lectures. This number has increased after COVID19 to 40 %, yet another sign of the negative impact of the pandemic on online lecturing. This inference is unrelated to the quality of the recordings which was deemed high. Finally, the importance of meaningful extended lecture notes to complement the recordings is highlighted.